Non-Muscle Myosin IIA (Myh9) is in the Nucleus of S-Phase Entering NT2-D1 Cells - Onganía, Gabriela Naum-; Poma, Rolando Rivera- (Journal of Nutritional Therapeutics, 2018)
Non-muscle myosin IIA is a cytoplasmic protein that works in concert with F-actin to produce cell movement. The heavy chain of this protein is codified by the MYH9 gene. The presence of motor proteins as myosin or mono and F-actin and their role in transcription has recently been observed. Prep1–the transcription factor of HOXB genes– constitutes a dimer with Pbx1, which induces HOXB gene expression. Prep1 has been found purifying with β-actin and Myh9. HOXB transcription initiates when cells enter in S-phase, during which DNA duplication and transcription occur at the same time. Here, we have shown that Myh9 co-localizes with Prep1 in the nucleus and in the periphery of the nucleolus in S-phase NT2-D1 cells. Furthermore, we have shown that Myh9 purifies with Pbx1 from nuclear extracts of S-phase entering NT2-D1 cells –and not from cytoplasmic extracts. Taking into account these results, we conclude that Myh9 is in the nucleus of the S-phase entering NT2-D1 cells and might have a role in HOXB transcription.